The application and effects of winglets on wind turbines - Gustafsson, Alexander; Häggström, Felicia; Johansson, Axel; Lanner, Cesar; Suomi Forssblad, Joacim (My University, 2024)
Ongoing research in the field of horizontal-axis wind turbines (HAWT) is dedicated to enhancing efficiency to maximize power generation. This bachelor’s thesis provides an in-depth exploration of the impact of blade modifications, specifically the addition of winglets, on wind turbine performance. The study draws upon existing literature on winglets, utilizes Computational Aided Design (CAD), and use Computational Fluid Dynamics (CFD) simulations to investigate the effects comprehensively. Three distinct winglets, each featuring different cant angles, were examined and compared. All winglet configurations were oriented towards the pressure side of the blade, with their height set to 1.5% of the blade radius. Furthermore, a wind turbine configuration without winglets served as a baseline for comparative analysis. Results showed that regardless of winglet design, the overall power output decreased. The thrust force however experienced a higher decrease compared to the power output, resulting in an higher power to thrust ratio. Regarding the Turbulent Kinetic Energy (TKE), the winglets had no noticeable effect compared to the standard blades. Further, the pressure coefficient around the blades indicated that the addition of winglets resulted in a lower pressure area close to the hub, but remained rather similar at the tip of the blade. Results also showed that the addition of winglets increased the skin friction coefficient, implying a corresponding rise in drag force.
Keywords: Winglets; Wind turbine; Sustainability; CFD; Fluid Dynamics; Aerodynamics; power coefficient